Prestasi Akademik Mahasiswa Kedokteran: Peran Tidur, Organisasi, dan Jarak Tempuh - Lubis, Amalya Janani; Ima Maria; Sukrisno, Adi; Muktamiroh, Hikmah (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2025)
Introduction: Sleep quality, organizational activities, and commuting distance may influence students' academic performance. Poor sleep reduces concentration, organizational involvement consumes study time, and long commuting distances increase fatigue, all of which can ultimately affect students' academic achievement. Purpose: This study aims to analyze the relationship between sleep quality, organizational activities, commuting distance, and the Grade Point Average (GPA) of the 2021 cohort of medical students at UPN Veteran Jakarta. Methods: A cross-sectional study was conducted with 118 respondents selected through simple random sampling. Data were collected using the Pittsburgh Sleep Quality Index (PSQI) questionnaire, along with information on organizational participation, commuting distance, and GPA. Data was analyzed using the Spearman test. Results: Most respondents had good sleep quality (82.2%), participated in 1–2 organizations (71.2%), lived within 1 km commuting distance (55.1%), and achieved a GPA categorized as very satisfactory (65.3%). There is no significant relationship between sleep quality and GPA (p=0.727) or between organizational activities and GPA (p=0.316). However, a significant relationship was found between commuting distance and GPA (p = 0.039; r = -0.191), with students living farther away tending to have lower GPAs. Conclusion: The results emphasize the importance of effective time management and residential location in enhancing students' academic success